Low-temperature isotopic fractionation of uranium - Stirling, C; Andersen, M; Potter, E; Halliday, A (2007)
Uranium is the heaviest naturally occurring element and isotope fractionation between 235U and 238U is not normally considered significant given the small ∼ 1% difference in mass. It is therefore usual to assume that 238U/235U is constant in the terrestrial environment and equal to 137.88. We have developed experimental protocols for the precise measurement of 235U/238U by multiple-collector ICPMS (MC-ICPMS) and have analyzed a suite of samples formed in a range of low-temperature environments. Using a high-purity 233U-236U double spike to internally monitor the large (percent-level) but essentially constant instrumental mass bias effects that are inherent to plasma source mass spectrometry, we are able to resolve variations in 235U/238U at the 0.4 epsilon level (2σ; 1 epsilon = 1 part in 10,000) on sample sizes comprising 50 ng of uranium. Here we demonstrate sizeable (13 epsilon units) natural variability in 235U/238U, exceeding the analytical reproducibility by more than an order of magnitude. Compositions that are both isotopically heavier and lighter than our terrestrial standard, by 4 and 9 epsilon units respectively, are observed. The largest excursions are found in speleothem samples. Furthermore, 235U/238U appears broadly correlated with 234U/238U in samples showing the most extreme isotopic compositions. The present study investigates the role of abiotic processes in fractionating 235U from 238U. Sequential leaching experiments of U-rich minerals indicate that mineral weathering is a possible mechanism by which 235U can be fractionated from 238U in groundwaters and incorporated into speleothems. The observed variability in 235U/238U indicates that uranium isotopes may offer the potential to monitor new reaction pathways, such as those activated during the redox transition between the U(IV) and U(VI) oxidation states. Experiments involving the redox transition of U(VI) to U(IV) in the presence of zero-valent zinc did not produce a resolvable shift in 235U/238U towards anomalous values, although fractionation need not occur if the reaction is governed by a fast kinetic process. Our observations have a direct impact on the U-series and U-Th-Pb chronometers, when applied to samples formed in low-temperature environments, as these chronometers currently assume an invariant 238U/235U equal to 137.88. © 2007 Elsevier B.V. All rights reserved.